Analytic Hierarchy Process in Asset Management Decisions for Public Service Agency Vocational Education - Bambang Setiawan; Torontuan Keban Yeremias; Wakhid Slamet Ciptono; Amirullah Setya Hardi (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2024)
The Ministry of Transportation’s Vocational Education Public Service Agency (BLU) has been underperforming in asset optimization, indicating inefficiencies in its asset management plan. This study critically examines existing asset management strategies and leadership effectiveness within the Ministry’s vocational education sector. Employing a phenomenological research approach, this investigation prioritizes a deep dove into asset management practices through semi-structured interviews and literature reviews. The findings highlight significant shortcomings in the BLU’s asset management and leadership, particularly in failing to meet its asset performance targets. These inadequacies are evaluated using ISO 55000 standards alongside human resources data, assessing five key areas: procurement and supply chain integration, innovative leadership, effective organizational structure, dynamic organizational culture, and human resource development. Analytical Hierarchy Process (AHP) analysis was used to prioritize issues under the Human Resources and Organization criteria. It identified asset management leadership as the most critical focus, with a weight of 0.40. This was followed by organizational culture at 0.23, competency management at 0.17, and both procurement and supply chain management and organizational structure at 0.10. The development of business units was highlighted as a priority over other strategies such as asset utilization and management collaboration. The regulatory framework guiding these strategies includes Minister of Finance Regulation 202/PMK.05/2022, which outlines four strategic asset utilization options. The analysis was proven to be consistent, with all priority weight matrices showing consistency ratios (CR) below 0.1, ensuring the reliability of the findings.